Dublin Anti-Bullying Self-Efficacy Models and Scales: Development and Validation - Sargioti, Aikaterini (Journal of interpersonal violence, 2023)
Literature on anti-bullying programs shows a growing consensus about promoting victims and bystanders’ self-efficacy against bullying, but provides no theoretical model nor measurement scale to assess the extent of achieving this aim. The current research aims to address these theoretical and empirical gaps by proposing the Dublin Anti-Bullying Self-Efficacy Models and Scales, using a convenience sample of 14-year-old students in Ireland (N = 1,100). After establishing both content and face validity, four separate scales were tested to measure anti-bullying self-efficacy beliefs among offline victims (20-item), online victims (20-item), offline bystanders (20-item), and online bystanders (20-item). Thereafter, four separate exploratory factor analyses of the scale items were followed by reflective measurement analyses of their internal consistency and construct (convergent and discriminant) validity. Results indicated sufficient psychometric properties of each scale measuring five dimensions of anti-bullying self-efficacy: recognition, emergency comprehension, responsibility, knowledge, and intervention. Further research is needed to test the proposed model and scale for assessing effectiveness of an anti-bullying program in promoting self-efficacy beliefs.